Merger and its impact on profitability of commercial banks - Mr. Suraj Khatiwada (Journal of Corporate Finance Management and Banking System, 2025)
The aim of this study was to investigate the impact of mergers and acquisitions on the profitability of Nepalese commercial banks. The research was conducted by analyzing various financial ratios that reflect profitability, employing a statistical approach. Two prominent commercial banks were selected as the sample, both of which had merged in the same fiscal year. The analysis focused on comparing pre-merger and post-merger profitability, utilizing a t-test to assess the significance of the merger's effects. Key profitability ratios, including Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), and Earnings Per Share (EPS), were evaluated to determine the influence of the merger on overall profitability. The findings indicated that the merger did not lead to an improvement in returns for the banks involved. This leads to the conclusion that mergers and acquisitions alone cannot guarantee an enhancement in the profitability of commercial banks. Instead, it is essential for regulatory authorities and stakeholders to take proactive measures to improve the financial health of banks without solely relying on mergers as a solution. Policymakers should consider implementing strategies that focus on the operational efficiency, risk management, and customer service quality of banks, which can contribute to sustaining profitability in a competitive environment.